Raw materials supply chain for rubber products : overview of the global use of raw materials, polymers, compounding ingredients, and chemical intermediates - Dick, John S.; Rader, Charles P.; ScienceDirect eBooks (Cincinnati : Hanser Publications, 2014)
The rubber industry is a vital part of the world economy. In this age of constantly changing economics and raw material "shortages of the week," this book should help the reader understand the overall technical and economic problems that are emerging which are beginning to affect the overall availability of many raw materials, chemical intermediates and final rubber products on the world scene. This book is truly unique in that it is the only one that traces all the important organic and inorganic synthesis routes for the manufacture of synthetic rubbers, various fillers, plasticizers, oils, curatives, antidegradants, adhesion promoters, flame retardants, tackifiers, and blowing agents through their respective intermediates to the base raw materials from earth extractions and agriculture.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Rubber chemicals; Rubber industry and trade; Rubber -- Additives; Supply and demand; Rubber -- Additives; Rubber chemicals; Rubber industry and trade; Supply and demand; TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; Electronic books